Facing India - Beil, Ralf; Ruhkamp, Uta; Kunstmuseum Wolfsburg, Wolfsburg (Berlin : Hatje Cantz Verlag GmbH, 2018)
Galhotra, Vibha ; Kher, Bharti ; Potnis, Prajakta ; Kallat, Reena Saini ; Sen, Mithu ; Shah, Tejal
Facing India, Kunstmuseum Wolfsburg, Wolfsburg, April 29 - October 7, 2018
boek
Keywords: India